Agency Problems and Endogenous Investment Fluctuations - Favara, Giovanni (Review of Financial Studies, 2012)
This article proposes a theory of investment fluctuations in which the source of the oscillating dynamics is an agency problem between financiers and entrepreneurs. In the model, investment decisions depend on entrepreneurs' initiative to select investment projects ex ante, and financiers' incentive to control entrepreneurs ex post. Too much control discourages entrepreneurial incentive to initiate new investment, whereas too little control jeopardizes its productivity. This initiative-control trade-off is capable of generating endogenous reversal of investment booms, induced by an ongoing deterioration of project profitability. Investment fluctuations may arise even though no external shocks hit the economy and agents are perfectly rational. The Author 2012. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oup.com., Oxford University Press.